2012
DOI: 10.2139/ssrn.2065904
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Correlation Dynamics in Sector Allocation

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent AbstractThis paper assesses the economic value of modelling conditional correlations for mean-variance portfolio optimization. Using sector returns in three major markets we show that the predictability of models describing empirical regularities in correlations such as time-variation, asymmetry and structural breaks leads to significant performance gains over the static covariance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…The decreasing DCC effects between Greek and the remaining EU countries during the crisis period are in sharp contrast to the unconditional correlations reported in Table 2. This shows the importance of modelling equity returns dynamically when the static correlations may portray misleading patterns (Kalotychou et al (2014)). It has been shown in Colacito et al (2011) that the efficiency improvements in the estimation of dynamic correlations are even higher when specification allows estimation of slow moving long run component.…”
Section: European Market Short Run Integration Patternsmentioning
confidence: 99%
See 2 more Smart Citations
“…The decreasing DCC effects between Greek and the remaining EU countries during the crisis period are in sharp contrast to the unconditional correlations reported in Table 2. This shows the importance of modelling equity returns dynamically when the static correlations may portray misleading patterns (Kalotychou et al (2014)). It has been shown in Colacito et al (2011) that the efficiency improvements in the estimation of dynamic correlations are even higher when specification allows estimation of slow moving long run component.…”
Section: European Market Short Run Integration Patternsmentioning
confidence: 99%
“…A higher association between the volatility of country X and the bivariate correlation of country X with country Y will stipulate simultaneous discounting of profits under poor market conditions and the exacerbated need to manage the integrated risk or to insure against this spiral risk. Studying this relationship is important given literature has identified that asset allocation strategies which time/benchmark dynamic volatility (Fleming et al (2001) or dynamic correlations (Kalotychou et al (2014)) could yield economically higher profits. Kalotychou et al (2014) reports that risk-averse investor could pay substantially higher fees to reap greater economic benefits of a richer correlation specification such as the DCC model.…”
Section: Among Others)mentioning
confidence: 99%
See 1 more Smart Citation
“…Primary sources of industry momentum returns are uncertain, and proposed explanations relate mainly to either delayed reaction to the traditional Fama‐French factors (Du and Denning, 2005), firm productivity (Chen et al ., 2007), time‐varying serial correlation (Du and Watkins, 2007), industry growth (Safieddine and Sonti, 2007), structural changes (Chui et al ., 2003; Kalotychou et al ., 2014) and herding (Demirer et al ., 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In our case, we opt for using the Asymmetric Dynamic Conditional Correlation GARCH model proposed by Cappiello, Engle, and Sheppard (). The choice of this model is based on the results of Gupta and Donleavy (), Kalotychou, Staikouras, and Zhao (), Zhou and Nicholson (), Yuan et al (), and Badshah () who show that modelling covariance asymmetry on the basis of the ADCC model contributes significantly to the economic value of the model due to the fact that conditional volatility, and the correlation of financial returns, tends to rise more after negative return shocks than after positive ones of the same size.…”
Section: Theoretical Backgroundmentioning
confidence: 99%